ZERO : Bildvorstellungen einer europäischen Avantgarde 1958-1964. - Perucchi-Petri, Ursula; Weitemeier-Steckel, Hannah; Gomringer, Eugen (Zürich : Kunsthaus Zürich, 1979)
Aubertin, Bernard ; Bartels, Hermann ; Castellani, Enrico ; Dorazio, Piero ; Fontana, Lucio ; Goepfert, Hermann ; Graubner, Gotthard ; Holweck, Oskar ; Klein, Yves ; Lo Savio, Francesco ; Mack, Heinz ; Manzoni, Piero ; Mavignier, Almir ; Megert, Christian ; Piene, Otto ; Schoonhoven, Jan ; Tinguely, Jean ; Uecker, Günther ; Verheyen, Jef ; de Vries, Herman
ZERO : Bildvorstellungen einer europäischen Avantgarde 1958-1964, Kunsthaus Zürich, 1. Juni bis 5. August 1979
Duits
kunstcatalogus
Keywords: Zero